Birds of prey - Barrett, Norman S. (New York : F. Watts, 1991)
A look at such predatory birds as eagles, vultures, and owls and how their hunting methods differ.
Includes index.
4.9
3-5.
3-6
Keywords: Birds of prey -- Juvenile literature; Birds of prey; Predatory animals; Birds of prey; Predatory animals